2021
DOI: 10.3389/fcell.2021.638798
|View full text |Cite
|
Sign up to set email alerts
|

More Human BM-MSC With Similar Subpopulation Composition and Functional Characteristics Can Be Produced With a GMP-Compatible Fabric Filter System Compared to Density Gradient Technique

Abstract: BackgroundMesenchymal stromal cells (MSCs), multipotent progenitors that can be isolated from a variety of different tissues, are becoming increasingly important as cell therapeutics targeting immunopathologies and tissue regeneration. Current protocols for MSC isolation from bone marrow (BM) rely on density gradient centrifugation (DGC), and the production of sufficient MSC doses is a critical factor for conducting clinical MSC trials. Previously, a Good Manufacturing Practice (GMP)–compatible non-woven fabri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…For the following passages, the projected MSC yield was calculated according to the formula N = N 0 × 2 n , where N is the projected MSC yield at end of the respective passage, N 0 is the projected MSC yield at P0, and n are the cumulative population doublings (cPDs) of the respective passage, i.e., number of cumulative doublings occurring in this passage. For the calculation, we used representative cPDs for MSCs as reported previously [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…For the following passages, the projected MSC yield was calculated according to the formula N = N 0 × 2 n , where N is the projected MSC yield at end of the respective passage, N 0 is the projected MSC yield at P0, and n are the cumulative population doublings (cPDs) of the respective passage, i.e., number of cumulative doublings occurring in this passage. For the calculation, we used representative cPDs for MSCs as reported previously [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, this methodology requires skilled manual dexterity and entails a prolonged duration for the isolation of cells (Grisendi et al, 2010;Yamamoto et al, 2015;Zhu & Murthy, 2013). Alternatively, the evaluation of the bone marrow collection kits for Use premixed commercialized differentiation kits hMSC isolation has been a subject of high interest (Anasiz, 2018;Capelli et al, 2009;Lopes et al, 2020;Otsuru et al, 2013;Spohn et al, 2021). For clinical indications, harvested bone marrow from a suitable donor is pooled and filtered through the bone marrow collection kit to remove residual fat, bone chips, and clots (McDaniel et al, 2017).…”
Section: Commentary Background Informationmentioning
confidence: 99%
“…Recently, a fully automated and closed ficoll system has been applied to harvest cells from bone marrow (BM), and a recent report analyzing a GMP-compatible nonwoven fabric filter system revealed that it could potentially increase isolated cell numbers without altering the properties of MSCs. 22 Nevertheless for different cell types and production processes, it is usually necessary to customize different automation equipment, greatly increasing capital investment and time consumption. 23 Furthermore, calibration of custom equipment and verification of GMP compliance are timeconsuming and labor-intensive processes.…”
Section: Automation and Environmental Controlmentioning
confidence: 99%
“…For well‐defined procedures, especially those for late‐stage clinical trials, it is preferable to maintain the entire manufacturing process in a closed system. Recently, a fully automated and closed ficoll system has been applied to harvest cells from bone marrow (BM), and a recent report analyzing a GMP‐compatible nonwoven fabric filter system revealed that it could potentially increase isolated cell numbers without altering the properties of MSCs 22 . Nevertheless for different cell types and production processes, it is usually necessary to customize different automation equipment, greatly increasing capital investment and time consumption 23 .…”
Section: Current Development Of Gmp‐compliant Msc and Exosome Manufac...mentioning
confidence: 99%